2013
DOI: 10.5194/acp-13-933-2013
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol particle measurements at three stationary sites in the megacity of Paris during summer 2009: meteorology and air mass origin dominate aerosol particle composition and size distribution

Abstract: During July 2009, a one-month measurement campaign was performed in the megacity of Paris. Amongst other measurement platforms, three stationary sites distributed over an area of 40 km in diameter in the greater Paris region enabled a detailed characterization of the aerosol particle and gas phase. Simulation results from the FLEXPART dispersion model were used to distinguish between different types of air masses sampled. It was found that the origin of air masses had a large influence on measured mass concent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
115
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 111 publications
(137 citation statements)
references
References 58 publications
20
115
1
1
Order By: Relevance
“…In all, 70 % of the OA was found to be transported from regional sources during both summer and winter. Freutel et al (2013) found that the concentrations of secondary species such as oxygenated OA, nitrate and ammonium during the summer MEGAPOLI campaign were quite similar for the three measurement sites in Paris, indicating the dominance of regional transport. Significant levels of secondary species were transported to Paris when the corresponding air masses originated from continental Europe.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In all, 70 % of the OA was found to be transported from regional sources during both summer and winter. Freutel et al (2013) found that the concentrations of secondary species such as oxygenated OA, nitrate and ammonium during the summer MEGAPOLI campaign were quite similar for the three measurement sites in Paris, indicating the dominance of regional transport. Significant levels of secondary species were transported to Paris when the corresponding air masses originated from continental Europe.…”
Section: Introductionmentioning
confidence: 87%
“…This underestimation of local sources (almost 0.2 µg m −3 for summer and winter) could be explained by the behavior of fresh POA. Both the measurement-based studies of Beekmann et al (2014) and Freutel et al (2013) found that almost 62 % of the OA in the center of Paris was HOA (Primary Organic Aerosol) and cooking OA and 38 % was oxygenated OA. The discrepancy between the measurements and the model can be explained by the cooking emissions which have not been included in the PMCAMx inventory used in this study.…”
Section: Comparison Of Psat Results and Observation-based Estimatesmentioning
confidence: 99%
“…For this campaign, measurements of organic carbon (OC), elemental carbon (EC) , and the most common ions are available. Finally, we have also analyzed 12 filter samples collected in Paris during summer 2009 and winter 2010, where concomitant online HR-ToF-AMS PM 1 measurements are available (Crippa et al, 2013a, b, c;Freutel et al, 2013).…”
Section: Aerosol Samplingmentioning
confidence: 99%
“…Consequently, current data sets are typically limited to few weeks and specific sites or measurements from mobile platforms . Recently, a robust, less expensive, Aerosol Chemical Speciation Monitor (ACSM, Ng et al, 2011b) and a time-of-flight aerosol chemical speciation monitor (ToF-ACSM, Fröhlich et al, 2013Fröhlich et al, , 2015 were developed to overcome some of these shortcomings. However, the low mass resolution of these instruments reduces their utility.…”
mentioning
confidence: 99%
“…Details about this campaign, the sampling of the C-ToF-AMS, and comparison to co-located measurements can be found in Freutel et al (2013). As presented in Freutel et al (2013), both total mass concentration time series and average ensemble volume size distributions measured by the AMS agree within about 10-20 % with respective measurements of colocated instruments. For this dataset, from 107 734 singleparticle events, 26 123 single-particle mass spectra could be retrieved after applying the criteria described above.…”
Section: F Freutel Et Al: Quantitative Single-particle Analysis Witmentioning
confidence: 57%